(untitled) (Journal of Laboratory Animal Science, 2024)
Laboratory animals are being used widely in the research and development organizations and hence their welfare is of a great concern. The welfare of laboratory animals varies in a continuum between the countries in the world and are linked to their cultural, societal and religious practices. There is a need for very good laboratory animal welfare in India and also countries for the advancement of scientific knowledge and benefit of the human kind. The status of the welfare of the laboratory animals used for research in India was discussed and also the way forward is explained.